Food microbiology : an introduction - Matthews, Karl R.; Kniel, Kalmia E.; Montville, Thomas J. (ASM Press, 2017)
Food Microbiology clarifies complex topics in the field of food microbiology and encourages students to venture beyond memorization and think critically to gain a broader conceptual understanding of food microbiology and acquire the understanding and skills necessary to ensure the safety of tomorrow's food supply.